Early experience of aortic surgery during the COVID‐19 pandemic in the UK: A multicentre study. Issue 3 (13th January 2021) - Lopez‐Marco, Ana; Harky, Amer; Verdichizzo, Danilo; Hope, Emma; Rosser, Barbara; McPherson, Iain; Kelly, Ronan; Holland, Luke; Ye Oo, Aung; ,
Abstract: Background: A significant restructuring of the healthcare services has taken place since the declaration of the coronavirus disease 2019 (COVID‐19) pandemic, with elective surgery put on hold to concentrate intensive care resources to treat COVID‐19 as well as to protect patients who are waiting for relatively low risk surgery from exposure to potentially infected hospital environment. Methods: Multicentre study, with 19 participating centers, to define the impact of the pandemic on the provision of aortovascular services and patients' outcomes after having adapted the thresholds for intervention to guarantee access to treatment for emergency and urgent conditions. Retrospective analysis of prospectively collected data, including all patients with aortovascular conditions admitted for surgical or conservative treatment from the 1st March to the 20th May 2020. Results: A total of 189 patients were analyzed, and 182 underwent surgery. Diagnosis included: aneurysm (45%), acute aortic syndrome (44%), pseudoaneurysm (4%), aortic valve endocarditis (4%), and other (3%). Timing for surgery was: emergency (40%), urgent (34%), or elective (26%). In‐hospital mortality was 12%. Thirteen patients were diagnosed with COVID‐19 during the peri‐operative period, and this subgroup was not associated with a higher mortality. Conclusions: There was a significant change in service provision for aortovascular patients in the UK. Although the emergency and urgent surgical activity were maintained, elective treatment was minimal during early months of the pandemic. The preoperative COVID‐19 screening protocol, combined with self‐isolation and shielding, contributed to the low incidence of COVID‐19 in our series and a mortality similar to that of pre‐pandemic outcomes.